THE INFLUENCE OF SERVICE QUALITY AND MEDICAL STAFF WORKLOAD ON PATIENT SATISFACTION IN THE EMERGENCY DEPARTMENT AT KASIH IBU HOSPITAL SURAKARTA - Alexander Nugroho Sulistya Wijoyo; Kosasih; Etty Sofia Mariati; Vip Paramarta (RADJA PUBLIKA, 2026)
The Emergency Department (ED) is a critical hospital unit that requires fast, accurate, and high-quality services due to its direct involvement in emergency patient care. Patient satisfaction in the ED is influenced by the quality of services provided as well as the workload borne by medical staff. This study aims to analyze the effect of service quality and medical staff workload on patient satisfaction at the Emergency Department of Kasih Ibu Hospital Surakarta, both partially and simultaneously. This research employs a quantitative method with a survey approach. The study population consists of patients treated in the Emergency Department, with samples selected based on predetermined criteria. Data were collected using questionnaires measuring service quality dimensions (tangible, reliability, responsiveness, assurance, and empathy), medical staff workload, and patient satisfaction. Data analysis was conducted using descriptive analysis and multiple linear regression. The results indicate that service quality has a positive and significant effect on patient satisfaction, medical staff workload has a negative effect on patient satisfaction, and both service quality and workload simultaneously have a significant effect on patient satisfaction. These findings highlight the importance of improving service quality and managing medical staff workload effectively to enhance patient satisfaction in the Emergency Department.